The Multi-Voxel MRS of Glioma: Glycine is a Suitable Biomarker for Tumor Grading - Hossein Taheri; Simin Hemati; Reza Moghareabed; Mohammadbagher Tavakoli; Ali Forouzmehr; Safura Mozafari; Negar Abdi; Yasaman Nilie; Hamed Taheri (Advanced Biomedical Research)
Background: The goal of this study was to evaluate the role of different metabolites such as glycine, choline (Cho), NAA, and creatinine (Cr) in the grading of glioma in the multi-voxel MRS. Materials and Methods: Thirty-five patients who suffered from glioma, according to their pathologic and clinical findings, were included in this study. In this work, the paraffin-embedded brain tissues of patients were studied by four expert pathologists. Then, the contrast enhancement T1-weighted (T1W) images and also multi-voxel MRS were performed for the patients. The volume of interests (VOIs) were drawn around the tumors, which may lead to preventing the impact of other parts of the brain in the metabolite analysis. Then, the correlation between the studied metabolites was calculated and the relationship among them was evaluated. Results: The correlation between glycine and other studied metabolites (Gly/NAA, Gly/Cho, Gly/Cr) for high-grade patients (4.28 ± 1.23, 4.12 ± 1.74, and 4.56 ± 1.98, respectively) was higher than low grades (2.69 ± 1.17, 2.73 ± 1.26, and 2.41 ± 1.34, respectively) (P = 0.716). Furthermore, the Cho/Cr, Cho/NAA for high grades (2.97 ± 1.23 and 2.58 ± 1.67) was higher than low grades (2.34 ± 1.76 and 1.98 ± 1.01, respectively). Also, the Cr/NAA for high grades (2.72 ± 1.87) was higher than low grades (2.41 ± 1.43), but it was not significant (P = 0.639). Conclusion: Evaluation of the correlation between glycine and other metabolites for glioma tumors in multi-voxel MRS is proposed because it would seem that glycine may have a positive role in glioma grading.